Physico-chemical soil attributes under conservation agriculture and integrated soil fertility management - Mutuku, E.A.; Vanlauwe, Bernard; Roobroeck, D.; Boeckx, P.; Cornelis, Wim M. (Springer, 2021)
Conservation Agriculture (CA) and Integrated Soil Fertility Management (ISFM) have been promoted in Sub Saharan Africa as a means to improve soil quality. A four season research (March, 2017 to March, 2019) was conducted to evaluate CA-based treatment, no tillage with residue retention (NTR), ISFM-based treatment, conventional tillage with use of manure (CTM), a combination of CA + ISFM, no tillage with residue retention and use of manure (NTRM) and a control, (C) on soil quality attributes. In the two locations (sub-humid and semi-arid) the effect of soil fertility gradients (high and low) were considered. Trials were set out using a one farm one replicate randomized design. In either high or low fertility fields, soil chemical and physical properties were significantly different between the control and NTR, CTM and NTRM with no significant differences between NTR, CTM and NTRM. SOC was higher under NTR and NTRM practices, which consequently had higher hydraulic conductivity, air permeability, mean weight diameter and available phosphorus. For all the treatments and in both locations, the low fertility fields had significantly lower agronomic use efficiency (AUE) compared to the high fertility fields. In both soil types, plant available water capacity and relative water capacity values were below the recommended thresholds indicating low soil water uptake, suboptimal microbial activity and consequently low nutrient uptake which explains the observed low AUE.